Deuterated Aryl Alkyl Ethers Synthesis via Nucleophilic Etherification of Aryl Alkyl Ethers and Thioethers with Deuterated Alcohols - Li, Shuai; Wang, Xia; Yang, Xin-Ge; Yu, Gui-Quan; Wang, Xue-Qiang (Synlett, 2019)
A transition-metal-free etherification protocol that is capable of synthesizing deuterated ethers is described. A wide range of aryl alkyl ethers and thioethers were suitable for this transformation owing to the mild reaction conditions. Besides, a series of sterically bulky deuterated alcohols were successfully incorporated into cyano-substituted arenes. The results of mechanistic studies suggested this reaction might take place via nucleophilic aromatic substitution pathway.
Keywords: deuterium; ether; thioether; etherification; nucleophilic aromatic substitution